THE USAGE OF PAUSE PROCEDURE METHOD DURING DISCUSSION BASED LESSONS - Turdiyeva Zahro Mirsoliyevna (TADQIQOTLAR, 2025)
Abstract Discussion-based lessons have gained prominence as a dynamic and interactive teaching  approach  that  fosters  critical  thinking,  collaborative  learning,  and  active student engagement. This article explores the theoretical and practical aspects of using discussion-based  lessons  in  educational  settings.  It  highlights  their  benefits  in developing communication skills, deepening subject comprehension, and enhancing problem-solving abilities. Additionally, the article addresses potential challenges and offers strategies for effective implementation. By analyzing case studies and relevant research, the study emphasizes the transformative role of discussion-based lessons in both traditional and modern classrooms.